The Effects of Leader-Member Exchange and Fun at Work on Work Engagement and Deviant Workplace Behavior in Indonesian Telecommunication Company - Luthfi Al Hakim , Muammar; W. Soetjipto, Budi (KnE Social Sciences, 2020)
This study was conducted to see the effect of leader-member exchange and fun at work on work engagement and deviant workplace behavior in Indonesian Telecommunication Company. Respondents are permanent employees of Telkom Indonesia Company located at the headquarters involving 130 respondents. The data were collected using a set of questionnaires and were analyzed using SEM technique with LISREL 8.80 application. The results showed that leader-member exchange has a positive significant effect on fun at work and work engagement and negative significant effect on deviant workplace behavior. In addition, this study also found that fun at work has a positive and significant effect on work engagement but does not have a significant effect on deviant workplace behavior. This study also compared the direct influence of leader-member exchange on work engagement and deviant workplace behavior with the indirect one through fun at work. Keywords: leader-member exchange, fun at work, work engagement and deviant workplace behavior